A Study on Two Dimensional (2D) Piezoelectric Semiconductor Materials: A Review - GYAN, MICHAEL (University of Thi-Qar Journal of Science, 2025)
This study explores the field of two-dimensional (2D) piezoelectric semiconductor materials, offering an in-depth analysis of their distinctive properties, synthesis techniques, and practical applications. Piezoelectricity, the generation of electric charge in response to mechanical stress is well-documented in bulk materials but has recently gained renewed attention with the development of 2D materials. These semiconductors exhibit unique characteristics, including exceptional mechanical flexibility, tunable electrical properties, and nanoscale control, which position them as promising candidates for advanced technologies. The paper examines the principles and mathematical models governing piezoelectric behavior, focusing on the distinctions between in-plane and out-of-plane effects in 2D systems. It further evaluates their potential applications in areas such as sensors, energy harvesting devices, and nanoelectronics. By synthesizing recent advancements, this study provides critical insights into the opportunities and challenges within this dynamic field, paving the way for the design of innovative devices and technologies.